Presentation of “living being” in early Indian Buddhism and its ethical implications - Ditrich, Tamara (Asian studies, 2023)
This article focuses on the presentation of the notion of “living being” and its link to ethics in the Pali Buddhist canon and its commentaries. This objective is achieved by examining the key Pali terms that refer to “living being” (i.e., satta, pa?a, and bhuta) in different contexts with the aim of identifying their sematic ranges. The article then discusses how the notion of “living being” in the Pali sources can be situated within the main doctrinal models developed in early Buddhism such as the six sense bases (ayatana), dependent origination (paticcasamuppada), and the Abhidhammic presentation of cognition, which are linked to a larger ethical framework that axiomatically repudiates the existence of a human “self” as the centre of all analysis. Instead, complex systems that link all living beings serve as the foundation for Buddhist praxis, and lead to a new understanding of the lived experience, which is founded on an ethics of behaviour, centred around non-vi-olence or the non-harming of all beings. The article concludes by exploring the important contribution of Buddhist ethics to the current environmental challenges by underscoring the essential role played by the doctrine of non-self (anatta) as the very source and foun-dation of an ethical stance from which ethical actions can proceed.
Keywords: “living being” in ancient India; early Buddhist ethics; Pali terms satta, pa?a and bhuta; palijski termini satta, pa?a in bhuta; plants in Theravada Buddhism; pojem “živega bitja” v stari Indiji; rastline v theravadskem budizmu; Theravada Buddhism; theravadski budizem; zgodnja budistična etika